SIMILARITIES AND DIFFERENCES OF ADJECTIVE DEGREE IN ENGLISH AND UZBEK LANGUAGE GRAMMAR - MUSTAFAEVA NARGIZA (TADQIQOTLAR.UZ, 2024)
This paper examines the grammatical structures for expressing degrees of adjectives in English and Uzbek, two languages with distinct linguistic backgrounds. The study explores the similarities and differences in how these languages utilize morphological and syntactic means to convey comparative and superlative forms of adjectives. In English, the comparative and superlative degrees are typically formed through the addition of suffixes (-er, -est) or the use of the adverbs "more" and "most." In contrast, Uzbek employs a combination of suffixes, particles, and periphrastic constructions to indicate adjective comparison. The analysis highlights key points of divergence, such as the Uzbek system's reliance on case marking and the availability of alternative comparative structures.The paper also discusses the pragmatic functions and semantic nuances associated with the various adjective degree forms in both languages. Factors like language register, semantic classes of adjectives, and discourse context are considered in examining how speakers leverage these grammatical resources. The findings contribute to the cross-linguistic understanding of adjectival gradation, with implications for language typology, second language acquisition, and translation studies. The comparative approach sheds light on the diverse grammatical strategies languages employ to encode the comparative and superlative meanings conveyed by adjectives.